2007
DOI: 10.1002/hipo.20306
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine prevents disruption of the late phase LTP‐related molecular cascade in adult‐onset hypothyroidism

Abstract: We have shown previously that chronic nicotine treatment reverses adult-onset hypothyroidism-induced impairment of late-phase long-term potentiation (L-LTP) in area CA1 of the hippocampus. In the present study, basal and stimulated levels of signaling molecules essential for the expression of L-LTP were determined in area CA1. Immunoblots analysis showed that chronic nicotine treatment of hypothyroid rats prevented the reduction in the basal protein levels of adenylyl cyclase I (ACI), mitogen-activated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Several lines of evidence have suggested that BDNF is involved in the L-LTP and long-term memory (Barco et al, 2005;Alzoubi et al, 2007b). L-LTP is impaired in knockout mice and mice with mutations in the BDNF receptor (Minichiello et al, 2002;Pang and Lu, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence have suggested that BDNF is involved in the L-LTP and long-term memory (Barco et al, 2005;Alzoubi et al, 2007b). L-LTP is impaired in knockout mice and mice with mutations in the BDNF receptor (Minichiello et al, 2002;Pang and Lu, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Standard procedures for in vivo recording from the Cornu Ammonis field 1 (CA1) brain region of anesthetized rats were performed as described (Alzoubi et al, 2007b). Rats were anesthetized with urethane (1.2 g/kg i.p.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…Seventeen days after implantation surgery, in vivo electrophysiological recordings from area Cornu Ammonis 1 (CA1) of the hippocampus was accomplished as described [24, 25]. Briefly, rats were urethane-anesthetized (1.2 g/kg, i.p., Sigma Aldrich, USA) and two holes were stereotaxically drilled for placing the stimulating and recording electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…The magnitude of E-LTP, evoked by one train of HFS (8 pulses of 400 Hz every 10 seconds, repeated 8 times), is quantified by changes in the field excitatory post-synaptic potential (fEPSP) slope and pspike amplitude recorded for 1 hour following HFS. The fEPSP slope and pspike amplitude represent synaptic strength and the number of neurons reaching firing threshold respectively [24, 25]. …”
Section: Methodsmentioning
confidence: 99%
“…L-LTP was induced in the CA1 region of the hippocampus, and five hours after MHFS, the rats were sacrificed and the septal and temporal parts of the right hippocampus were dissected out. As stated in the Method section, to minimize individual variation, the temporal side was used as an internal control [52,53,63,64].…”
Section: Levels Of Signaling Molecules During L-ltpmentioning
confidence: 99%